Children's Lived Experience of Poverty and Vulnerability in Kenya - Ngutuku, Elizabeth (Taylor & Francis, 2025)
Drawing from ethnographic research, this book presents children’s lived experience of poverty and vulnerability in Kenya. By taking the case of Siaya, Kenya, which has some of the lowest indicators of child well-being, the book presents children’s complex lived experience from three interlinked everyday spaces of the home, the school and support programmes. It argues that children’s experience is formed at the interstices of material lack, historically as well as politically located factors and the complex context of social relations. The book is anchored in an innovative methodology of listening softly to children’s voice. Aimed at fully capturing children’s experience, listening softly focusses on the different ways that children’s voice happen. The book challenges scholarship to go beyond multi-dimensionality and re-imagine children’s experience as complex and entangled, use methods that are attuned to capturing children’s messy experience of poverty, and be ‘widely awake’ in each intervention context to capture the emergent fluid experience of children. Presenting a non-linear, contextual, entangled and complex experience of poverty and vulnerability, this book will be of interest to scholars and students in the field of Poverty Studies, Development Studies, Childhood Studies, Social Policy, Critical studies, Human and Child Rights and African Studies.